Writing to Speech Conversion Application With Using an Android-Based Camera to Talk - Amin, Muhammad (International Conference on Sciences Development and Technology, 2023)
Talking and listening are the most efficient things for humans to do with each other communicate. Many people have difficulty communicating by speaking which is usually referred to as Speech Impairment. This application aims to make it easier for the deaf or people who have difficulty speak so that you can communicate well and correctly by speaking voice. The process of making this application was made using Android studio, mobile vision API, and Text To Speech. With the conversion application writing to speech using a camera for the Android-based speech impaired can It was concluded that the application could help speech impaired people and people people who have difficulty speaking communicate better and more effectively